The COMBAT project: Controlling and progressively minimizing the burden of vector-borne animal trypanosomosis in Africa [version 2; peer review: 3 approved] - (:unkn) unknown (My University, 2022)
Source Agritrop Cirad (https://agritrop.cirad.fr/601328/) * Autres projets (id;sigle;titre): 101000467;COMBAT;(EU) COntrolling and progressively Minimizing the Burden of Animal Trypanosomosis//
Keywords: African Research